Survey of Understanding Levels of Futsal Game Rules (Laws of The Game) on Futsal Extracurricular Participants - Labib Ramdhani; Hasan Basri (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2023)
This study aims to determine the level of understanding of the rules of the game of futsal (laws of the game) among students participating in futsal extracurricular activities for SMA/SMK in Rawalumbu District, Bekasi City. This research is a descriptive qualitative research. Data analysis techniques using quantitative descriptive presented in the form of a percentage. Based on the results of data analysis and discussion, it can be concluded that the level of understanding of the rules of the game of futsal (laws of the game) in futsal extracurricular participants throughout Rawalumbu District, Bekasi City in the